Knowledge, attitude and the use of ICT among ESL lecturers in UiTM Terengganu / Nazratul Akmal Awang @Hashim - Awang @Hashim, Nazratul Akmal (2015)
This study is a survey on 50 ESL lecturers of Universiti Teknologi Mara (UiTM) Terengganu pertaining to their ICT knowledge level and attitude towards ICT incorporation in the ESL class. Their level of ICT use in the ESL class and the challenges faced in incorporating ICT in the language class was also investigated. The entire sample of 50 comprises the population. A survey questionnaire was distributed to elicit information pertaining to the research issues mentioned above. Descriptive statistics indicated that the respondents’ knowledge level of ICT use, attitude towards ICT use and level of use in the ESL class was fairly satisfactory. However, the survey showed that they do face some challenges in implementing ICT concerning lack of knowledge for higher ICT applications and non-availability of technical support certain times. Further, the existence of any significant relationship between respondents’ ICT knowledge and attitude towards ICT in the ESL class and also their attitude towards ICT and their level of ICT use in the ESL class was investigated using inferential statistics. In both relationship test, the relationship was found to be strong and positive and the Pearson V level was above 0.5. The quantitative survey findings are supported by some interviews of five of the respondents. Future researchers should extent this study to other campuses of UiTM and also other universities in Malaysia for comparison purposes. Future researchers could also see the difference between age groups pertaining to ICT implementation in the ESL class.